Efficacy of serratiopeptidase after impacted third molar surgery: a randomized controlled clinical trial - Zaid Tamimi; Rola Al Habashneh; Islam Hamad; Mutasim al-Ghazawi; Ala' Abu Roqa'a; Hamza Kharashgeh (BMC, 2021)
Abstract Background Serratiopeptidase has been clinically used in controlling surgical and non-surgical inflammatory conditions. This study was conducted to assess the therapeutic effect of Serratiopeptidase in patients undergoing surgical removal of impacted mandibular third molar. Methods This randomized clinical trial investigated the efficacy of Serratiopeptidase and Paracetamol after surgical removal of impacted third molar for 5 days (n = 67) as compared with an equivalent dose of placebo and Paracetamol (n = 66). Outcome measures were reported pain, trismus and swelling using Laskin method. All outcome measures were recorded on days 0, 1, 2, 4, and 5 post-surgeries. Results In this clinical trail 133 patients (mean age 23 years, 54% female) completed the study. Baseline characteristics were comparable across treatment groups. Serratiopeptidase significantly improved trismus compared with control on the 4th day (27.30 ± 7.3 mm and 32.06 ± 7.7 mm, respectively (P < 0.001) Swelling markedly improved, The distance from the lower edge of the earlobe to the midpoint of the symphysis for cases vs control were 111.49 ± 8.1 mm and 115.39 ± 9.9 mm, respectively (P < 0.001). Reported pain, showed no statistical significance difference. Conclusion Serratiopeptidase resulted in better inflammation improvement than placebo over 5 days. Further studies are warranted to assess longer-term and clinical outcomes, as well as safety. Clinical relevance Serratiopeptidase administered postoperatively helps in improving trismus and swelling after removal of impacted lower third molars. Trial registration The study was registered in ClinicalTrial.gov under the number NCT02493179. Registered 1st of June 2015, https://clinicaltrials.gov/ct2/results?cond=serratiopeptidase .